The network form as a tool for improving the quality of education in the context of digitalization - Natal’ya V. Shlyakhtina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The modern educational environment in the conditions of the digital world considers the network form of implementation of educational programs as a tool for improving the quality of education. The network form of implementation of educational programs as an innovative reality in schools participating in the regional project Modern School is based both on the use of resources of several educational organizations and other institutions to solve the deficits of the basic organization itself. The network form provides an opportunity to maximize the use of material, technical and infrastructural resources updated through the supply of digital equipment and qualitatively new training of teaching staff. The paper substantiates the relevance of the network form implementation of the implementation of educational programs. The paper presents the results of quarterly monitoring of educational organizations that have established Education Centers and implement digital programs, including the network form and distance learning technologies. The subject of the study is educational activities of schools for the implementation of digital profile programs, including the online form. As a result of the study, the models of implementing educational programs in a network form using the equipment of the Education Centers are identified, and management solutions are proposed to improve the quality of implementing programs in a network form. The issues considered in the paper are very relevant at the present stage of the search for new grounds to improve the quality of education and new forms of quality management and the process of implementing programs in a network form. They are the subject of active discussion in the pedagogical community and can serve as material for use in pedagogical and managerial practice.